Criminal Life Courses in Context - Sanne Muurling; Evelien Walhout (Historical Life Course Studies)
The future of the Historical Sample of the Netherlands (HSN) will certainly include the enrichment of the foundational database with additional, new sources of information. In general, the HSN would highly benefit from current mass digitization projects involving citizen science. This essay proposes a pilot in linking 19th- and early 20th-century criminal records to HSN. In spite of the extensive state and parish registration documenting individual and family lives in close systematic detail, life course approaches to historical crime are less common. The large datasets necessary to conduct longitudinal life course research into deviant behaviour will facilitate both the analysis of criminality as an event and the scrutiny of the trajectories of individuals' lives leading up to their involvement in crime.